2012
DOI: 10.1063/1.4757599
|View full text |Cite
|
Sign up to set email alerts
|

Shock initiation of the tri-amino-tri-nitro-benzene based explosive PBX 9502 cooled to −55 °C

Abstract: We report a series of shock initiation experiments on PBX 9502 cooled to −55 °C. PBX 9502 consists of 95% dry aminated tri-amino-tri-nitro-benzene (TATB) and 5% poly-chloro-trifluoro-ethylene5 (Kel-F 800) binder. PBX 9502 samples were shock initiated by projectile impact from a two stage gas gun. Buildup to detonation was measured with 10 or more particle velocity gauges embedded at different depths in the sample. Three shock wave trackers measured the position of the shock front with time. Particle velocity v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…We can also compare C bulk at zero pressure with experimentally available data on shock velocity, U S , extrapolated to zero particle velocity, u p . For example, Gustavsen et al 44,45 obtained the shock adiabat of TATBbased formulation PBX 9502 (95% TATB and 5% Kel-F 800 binder) both for room temperature and for À55 C. We approximated their data by a linear dependence and obtained the value of C bulk to be equal to 3.05 km/s with the correlation coefficient R ¼ 0.989. It supports our estimations on sound speeds in TATB, at least determined at zero pressure.…”
Section: B Sound Speedsmentioning
confidence: 98%
“…We can also compare C bulk at zero pressure with experimentally available data on shock velocity, U S , extrapolated to zero particle velocity, u p . For example, Gustavsen et al 44,45 obtained the shock adiabat of TATBbased formulation PBX 9502 (95% TATB and 5% Kel-F 800 binder) both for room temperature and for À55 C. We approximated their data by a linear dependence and obtained the value of C bulk to be equal to 3.05 km/s with the correlation coefficient R ¼ 0.989. It supports our estimations on sound speeds in TATB, at least determined at zero pressure.…”
Section: B Sound Speedsmentioning
confidence: 98%
“…16,17 Among the inorganic nanoparticles, as a kind of new quasi-onedimensional functional material, CNTs have attracted intensive interest for a variety of applications in science and engineering during the past decade, [18][19][20][21][22] due to the excellent mechanical and physical properties, such as extremely high strength and stiffness, high thermal and electrical conductivity, and low density. The structure and properties of TATB-based PBX, such as pore structure and size distribution, 28,29 microstructural differences between virgin and recycled lots, 30 mechanical behavior, [31][32][33] shock initiation, 34,35 thermal expansion, 36,37 sensitivity, 38 moisture outgassing, 39 have been widely studied in the past years. 9-13 Yang et al 9 have found that with only 1 vol% of multiwalled carbon nanotubes (MWCNTs), creep resistance of PP can be signicantly improved with reduced creep deformation and creep rate at a long-term loading period without sacricing mechanical properties and weight penalty.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a small part of the increased sensitivity may be attributed to the increased porosity at higher temperatures, which results in more hot-spot ignition sites under shock compression. The increased sensitivity may also be attributed to a more rapid growth of these reacting hot spots, because the chemical decomposition is propagating in hotter C-1 material [4,5,10].…”
Section: Figurementioning
confidence: 99%
“…Another parameter that changes with temperature is the explosive density; the change in density is caused by the thermal expansion of C-1 during the heating process. The coefficient of thermal expansion for the ε phase of CL-20 is 0.00014/K in the range of 300-390 K [8]; after the ε→γ phase transition, the volume of C-1 is 6% larger [10]. The JWL EOS parameters of the reaction products were obtained by a cylinder test for the C-1 explosive.…”
Section: Numerical Simulationmentioning
confidence: 99%